"Captive Markets": the impact of kidnappings on corporative investment in Colombia (2005)
This paper measures the impact of crime on firm investment by exploiting variation in kidnappings in Colombia from 1996 to 2002. Our central result is that firms invest less when kidnappings target firms. We also find that aggregate crime rates-homicides, guerrilla attacks, and general kidnappings-have no significant effect on investment. This finding alleviates concerns that our main result may be driven by unobserved variables that explain both overall criminal activity and investment. Furthermore, kidnappings that target firms reduce not only the investment of firms that sell in local markets, but also the investment of firms that sell in foreign markets. Thus, an unobservable correlation between poor demand conditions and criminal activity is unlikely to explain the negative impact of firm-related kidnappings on investment. Our results are consistent with the hypothesis that managers are reluctant to invest when their freedom and life are at risk; however, we cannot completely discard alternative explanations.